CALPHAD-informed phase-field model for two-sublattice phases based on chemical potentials: η-phase precipitation in Al-Zn-Mg-Cu alloys. (March 2022) - Liu, Chuanlai; Davis, Alec; Fellowes, Jonathan; Prangnell, Philip B.; Raabe, Dierk; Shanthraj, Pratheek
Graphical abstract: Abstract: The electrochemical properties of high strength 7xxx aluminium alloys strongly depend on the substitutional occupancy of Zn by Cu and Al in the strengthening η -phase with the two-sublattice structure, and its microstructural and compositional prediction is the key to design of new generation corrosion resistant alloys. In this work, we have developed a chemical-potential-based phase-field model capable of describing multi-component and two-sublattice ordered phases, during commercial multi-stage artificial ageing treatments, by directly incorporating the compound energy CALPHAD formalism. The model developed has been employed to explore the complex compositional pathway for the formation of the η -phase in Al-Zn-Mg-Cu alloys during heat treatments. In particular, the influence of alloy composition, solute diffusivity, and heat treatment parameters on the microstructural and compositional evolution of η -phase precipitates, was systematically investigated from a thermodynamic and kinetic perspective and compared to electron probe microanalysis validation data. The simulated η -phase growth kinetics and the matrix residual solute evolution in the AA7050 alloy indicates that Zn depletion mainly controlled the η -phase growth process during the early stage of ageing, resulting in fast η -phase growth kinetics, enrichment of Zn in the η -phase, and an excess in residual Cu in the matrix. The gradual substitution of Zn by Cu atoms in the η -phase during the later ageing stage was in principle a kinetically controlled process, owing to the slower diffusivity of Cu relative to Zn in the matrix. It was also found that the higher nominal Zn content in alloys like the AA7085 alloy, compared to the AA7050 alloy, could significantly enhance the chemical potential of Zn, but this had a minor influence on Cu, which essentially led to the higher Zn content (and consequently lower Cu) seen in the η -phase. Finally, substantial depletion of Zn and supersaturation of Cu in the matrix of the AA7050 alloy was predicted after 24 h ageing at 120 ∘ C, whereas the second higher-temperature ageing stage at 180 ∘ C markedly enhanced the diffusion of Cu from the supersaturated matrix into the η -phase, while the matrix residual Zn content was only slightly affected.